Mechanical performance of lightweight brick at elevated temperature - Adnan, Suraya Hani; Pozi, Adriana Farniza; Osman, Mohamad Hairi; Ahmad Jeni, Mohamad Luthfi; Mohd Yassin, Nurain Izzati; Jamellodin, Zalipah; Abdul Hamid, Noor Azlina; Salleh, Norhafizah; A. Majid, Masni (Scopus Elsevier, 2021)
This study presents the production of lightweight concrete brick containing Expanded Polystyrene (EPS). The objective of this study is to determine the effectiveness of EPS as a substitute for sand in the concrete mix. The replacement percentage of EPS is 20%, 30%, 40% and 50% from the sand volume. Hardened brick density, compressive strength, water absorption and fire resistance test were conducted in order to examine the brick performance. The dimension of the brick is 215mm x103mm x 65mm. The total of samples for different testing were 60 samples of bricks where 30 samples were undergoing for density and compressive strength test with curing age 7 and 28 days, 15 specimens for water absorption test and 15 specimens for fire resistance test required. All brick samples were subjected to air curing. From the results, it is found that brick sample with 50% EPS is considered as lightweight brick because its density is 1435.71 kg/m3. The results indicated that increasing the volume of EPS causes significant reduction to compressive strength, water absorption and fire resistance of brick.